Implementation of SI-KEPPO Innovation to Increase Return Visits of Hypertension Patients at Public Health Center of Sobo, Banyuwangi: Implementasi Inovasi SI-KEPPO dalam Upaya Peningkatan Kunjungan Ulang Pasien Hipertensi di Puskesmas Sobo Banyuwangi - Essy Sonontiko Sayekti; Dewi Aminah; Kusnul Kotimah; Dodi Wijaya; Yulianingsih (KHD Production, 2024)
The key to managing hypertension is regular control visits to the community health center or other health facilities. These visits are critical in monitoring response to treatment, adjusting therapy if necessary, and providing education and support to the patient. Low compliance of hypertension patients with re-visits or regular control can hinder the success of hypertension management and increase the risk of complications. The SI-KEPPO (Automatic Reminder Message Group System) innovation aims to provide an effective solution in managing and arranging re-visits or reminding individuals or groups of contact time automatically via text messages or other messages. This activity is a community service aimed at doctors, nurses, administration staff and counter staff. A direct training is carried out on computers owned by the Community Health Center so that deficiencies and advantages are detected in the existing facilities at the Community Health Center. The material presented is an introduction to the program or innovation by explaining the use of the innovation, the preparations made and the procedures for implementing it. There were 1 doctor, 4 nurses, 1 medical center administration staff, 1 operator staff, and 1 counter staff who participate in community service activities. All participants were very enthusiastic about this training and it could increase the number of repeat visits for hypertensive patients.